Employment Transitions of Women in India: A Panel Analysis - Sudipa Sarkar; Soham Sahoo; Stephan Klasen (Institute of Labor Economics (IZA), 2017)
This study analyses employment transitions of working-age women in India. The puzzling issue of low labour force participation despite substantial economic growth, strong fertility decline and expanding female education in India has been studied in the recent literature. However, no study so far has looked into the dynamics of employment in terms of labour force entry and exit in this context. Using a nationally representative panel dataset, we show that women are not only participating less in the labour force, but also dropping out at an alarming rate. We estimate an endogenous switching model that corrects for selection bias due to initial employment and panel attrition, to investigate the determinants of women's entry into and exit from employment. We find that an increase in income of other members of the household leads to lower entry and higher exit probabilities of women. This income effect persists even after controlling for the dynamics of asset holding of the household. Along with the effects of caste and religion, this result reveals the importance of cultural and economic factors in explaining the declining workforce participation of women in India. We also explore other individual and household level determinants of women's employment transitions. Moreover, we find that a large public workfare program significantly reduces women's exit from the labour force.
Keywords: J21; J16; O15; 330; female labour force participation; employment transition; panel data; sample selection; attrition; India